(untitled) (Research, Society and Development, 2021)
This study aims to: Identify, in the literature, the role of nurses in humanized care for the elderly in primary care; Check the methods developed by nurses that provide humanized care for the elderly in primary care; Know the benefits of humanized care provided by nurses to the elderly. This research used the integrative literature review as a method, with quantitative, descriptive and exploratory data. Data selection took place on April 8, 2020, through articles indexed in the following databases: Database in Nursing (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online ( SciELO). Original articles, in Portuguese, national, available in full and free of charge, were included in the research. Theses, clippings from magazines and newspapers, letters to the editor, congress, abstracts and meta-analyses, in addition to articles inferior to the year 2014 and that did not meet the established objectives and issues, were excluded. After screening, 17 articles were selected that made up the final sample. There was a positive result of the data, noting that the role of nurses in the primary care setting in relation to fundamental humanized care. The publications allowed the realization of the variables, which were categorized in the discussion, namely: The role of nurses in humanized care for the elderly in primary care; Methods developed by nurses that provide humanized care for the elderly in primary care; Benefits of humanized care provided by nurses to the elderly. It was possible to understand the importance of the nurse’s role in humanized care for the elderly in primary care, the nurse is an indispensable professional in this context, contributing positively to the multidisciplinary team with an emphasis on the health of the elderly.